Interrelations Between Chlorophyll Fluorescence Parameters as a Tool for the Detection of Seasonal Changes in Photosystem II Kinetics in Two Strawberry (Fragaria X Ananassa Duch.) Cultivars (Global Journal of Science Frontier Research, 2015)
The aim of this study was to establish relationships between parameters of chlorophyll fluorescence in two strawberry cultivars in order to detect the seasonal changes in their photosystem II (PSII) kinetics. Parameters of chlorophyll fluorescence (CF) such as: Fo, Fm, Fv/Fm, Fo`, Fm`, qP, qN and Y were measured in mature leaves of two strawberry cultivars 'Teresa' and 'Honeoye' in a late spring and an early autumn. Fluorescence of dark-adapted leaf samples was measured in the laboratory at room temperature, with the use of a portable pulse amplitude modulation (PAM) fluorometer in fifteen replicates for each parameter. Relationships between CF parameters calculated on the basis of Pearson's correlation coefficients were highly differentiated in the analyzed cultivars and depended on the genotype and its specific response to the various environmental conditions characterizing both seasons of the year.
Keywords: correlation; environment; genotype; interaction; photosynthesis